A Deduplication -Aware similarity finding and removal system for Cloud Provider and Its Users - Reddy Pradeep, K; Sreehitha, G (International Journal of Computer Sciences and Engineering, 2025)
Data reduction has become increasingly very important in storage systems thanks to the explosive growth of digital information among the globe that has ushered among the large information era. In existing system cloud suppliers offer less method capability and thus displease their users for poor service quality. Therefore, it is vital for a cloud provider to select out applicable servers to provide services; such it reduces worth the most quantity as potential wherever as satisfying its users at the same time. Here the foremost disadvantage duplication therefore to beat of those problems we tend to tend to pick planned model. Throughout this paper, we tend to gift DARE, a low-overhead Deduplication-Aware likeness detection and Elimination theme that effectively exploits existing duplicate-adjacency information for terribly economical likeness detection in information deduplication based backup/archiving storage systems. Our experimental results and backup data sets show that DARE only consumes concerning 1/4 and 1/2 severally of the computation and classification overheads required by the conventional super-feature approaches whereas investigating 2-10% extra redundancy and achieving an improved turnout, by exploiting existing duplicate-adjacency information for likeness detection and finding the “sweet spot” for the super-feature approach.